PEMBELAJARAN MATEMATIKA MENGGUNAKAN LEMBAR KERJA SISWA (LKS) BERBASIS MASALAH - Chauriyah Dehani Tri P.N (MEJ (Mathematics Education Journal), 2017)
This research was conduct to describe mathematics learning plans using problembased worksheet, mathematics learning implementation using problem-based worksheet, and how was mathematics learning results using problem-based worksheet. This research met the essence of descriptively qualitative research. In this research, students of class VII-B MTs Muhammadiyah 1 Malang and researcher as source of the data, while teacher activites, students activites and study result as the product. Data was taken from teacher and students obsevation during learning process using problem-based worksheet. In addition, student study result. Analysis of activity of teachers and students is seen fromthe scores on the observation sheet and averaged to determine how much liveliness teachers and students during the learning process. Whereas, for the analysis of the test results of students' views of the thoroughness of the individual and classical. The completeness of individuals can be achieved if the learning outcomes of students achieving ≥75 maximum score of 100, while the classical completeness can be achieved if 75 % of the number of students in the class who have achieved a score of ≥75. The research outcome illustrate that mathematics learning using problem-based worksheet can be implemented in tune with the stages that were planned in the RPP. The teavher activities average is 3.59 in very good categories and student activity average include ingood categories with score 2.98. The students activity aspects consist of obsevation, questioning, reasoning, and communication. Mathematic learning result of using problem-based worksheet achieve the KKM in 76.47% classically.